2000
DOI: 10.1007/s001340000757
|View full text |Cite
|
Sign up to set email alerts
|

Influence of selenium supplements on the post-traumatic alterations of the thyroid axis: a placebo-controlled trial

Abstract: Selenium supplements increased the circulating Se levels. Supplementation was associated with modest changes in thyroid hormones, with an earlier normalisation of T4 and reverse T3 plasma levels. The addition of AT and zinc did not produce any additional change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 28 publications
0
65
0
4
Order By: Relevance
“…Therefore, it has been concluded that low selenium might also lead to a decreased 5 0 -deiodinase activity followed by low T3 production in humans. This was supported by an interventional trial in trauma patients where it was shown that a substitution with sodium selenite normalizes total T3 levels earlier compared with controls (16). No correlation between low T3 and selenium levels, however, was found in other studies in critically ill patients (35,36) or in the healthy population (37).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, it has been concluded that low selenium might also lead to a decreased 5 0 -deiodinase activity followed by low T3 production in humans. This was supported by an interventional trial in trauma patients where it was shown that a substitution with sodium selenite normalizes total T3 levels earlier compared with controls (16). No correlation between low T3 and selenium levels, however, was found in other studies in critically ill patients (35,36) or in the healthy population (37).…”
Section: Discussionmentioning
confidence: 87%
“…It has already been shown that in critically ill patients, selenium substitution leads to an earlier normalization of plasma T3 levels compared with controls (16) and that low plasma selenium levels correlate with low T3 levels (17). From these studies, it has been concluded that the main cause of low T3 levels might be the decreased activity of the selenoenzyme 5 0 -D1.…”
Section: Introductionmentioning
confidence: 99%
“…Globalement, les anti-oxydants ont un effet favorable sur la mortalité (RR 0,76, 95 % CI 0,64-0,91, p = 0,002) et la durée de ventilation (−2,63 jours, 95 %CI −3,16-−2,10, p < 0,0001) mais pas d'effet sur les complications infectieuses ou sur la durée de séjour [37]. Plusieurs études ont concerné l'apport de sélénium seul par voie intraveineuse [105,109,[112][113][114]. La supplémen-tation à des doses de 350 à 1000 g/j avait des effets favorables [105,109,112,116] alors que des doses beaucoup plus élevées semblaient délétères [113].…”
Section: éTudeunclassified
“…Plusieurs études ont concerné l'apport de sélénium seul par voie intraveineuse [105,109,[112][113][114]. La supplémen-tation à des doses de 350 à 1000 g/j avait des effets favorables [105,109,112,116] alors que des doses beaucoup plus élevées semblaient délétères [113]. La méta-analyse de ces études suggère que l'apport de sélénium par voie intraveineuse est associé à une tendance à la réduction de la mortalité, mais n'a pas d'effet sur les complications infectieuses ou la durée de séjour [37].…”
Section: éTudeunclassified
“…[73]. Die Autoren berichteten auch über eine etwas raschere Normalisierung der Schilddrüsenfunktion [74]. In einer anderen Studie senkte eine Tagesdosis von 100 µg Selen und 20 mg Zink die Infektionsrate bei älteren Patienten signifikant [75].…”
Section: Selen Als Kombinationsbehandlungunclassified